La parole de l’enfant victime de violences sexuelles : Une enquête au sein de tribunaux correctionnels français en 2010 - Marie Romero (Criminocorpus)
The word of the child victim is particularly delicate in cases of sexual violence. The fear of not being believed, the absence of a direct witness, the shame of talking about the facts suffered are as many obstacles to disclosure. This word is all the more important because in these cases, there is a vast stake around the evidence: absence of direct witness, absence of violence or physical trace, late denunciations, word of one against the other ... Also, from a corpus of cases of sexual violence tried in french correctional courts in the course of 2010, the article examines the judicial implications related to the release of the speech of the child victim (from the time of silence, to unveiling, to his revelation in court). It shows on the one hand that this word unveiled in court is complex and never neutral, especially in the case of intra-familial sexual violence; On the other hand, it can have a significant impact on the evidence, especially when the facts are disputed by the mis en cause.